Analysis of the Performance of a Dehulling System for Confectionary Sunflower Seeds - de Figueiredo, Ana Karina (2014)
Confectionary sunflower, which has a larger size and lower oil content than oilseed sunflower, has a considerable market, since it is used for birdfeed and human consumption. The characteristics of use of confectionary sunflower seeds require a dehulling process that is efficient in the removal of the hull and that also allows obtaining a product consisting mainly of whole kernels. Response surface methodology was used to determine an optimal combination of working conditions in the dehulling process of confectionary sunflower seeds. Optimization factors were impact speed, expressed in terms of the peripheral speed (28.3 - 41.9 m/s), and moisture content of the seeds (4% - 14%, dry basis—db). A central composite rotatable design (CCRD) was used to develop models for the responses (dehulling ability—DA and percentage of whole kernels—WK). Applying the desirability function method, the optimal values of the factors were determined using maximum WK and maximum DA as criteria. The results of the optimization technique suggest that by dehulling Mycogen 9338 confectionary sunflower seeds at 12.3% db and 32.5 m/s, the maximum values of DA and WK (72.6% and 63%, respectively) would be obtained. The moisture value defined as optimal determines a requirement of humidification of the seeds prior to dehulling, establishing the need for a technical and economic feasibility study.